COVID-US: a simplified cardiopulmonary ultrasound approach to use in suspected and confirmed COVID-19 - Marek Nalos (World Nutrition Journal, 2020)
Using ultrasonography to help diagnose, risk stratify and treat patients suffering from COVID-19 disease is therefore intuitive and imperative.